IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA SEKOLAH DASAR STUDI KASUS DI SDN PINELENG - Julien Chintya; Rati Anggraini Pontoh; Elisabeth Rosina Lantang (Jurnal Ilmiah Wahana Pendidikan, 2026)
This study aims to describe the implementation of the Think Pair Share (TPS) cooperative learning model in improving the critical thinking skills of elementary school students. The study used a qualitative approach with a case study. The subjects were fourth-grade teachers and 28 fourth-grade students at SDN Pineleng. Data collection techniques included participant observation, in-depth interviews, and documentation. Data validity was tested using source and technique triangulation. The results showed that: (1) TPS learning planning was carried out systematically through the development of lesson plans based on the Merdeka curriculum; (2) the implementation of the TPS model took place in three main stages: think (independent thinking), pair (pair discussion), and share (sharing with the class); (3) students' critical thinking skills experienced a significant increase, indicated by an increase in their ability to reason, reason, and summarize information. This study concludes that the TPS learning model is effective in elementary schools when supported by good classroom management and teacher scaffolding.